Range of Motion (ROM) Early Affecting The Ability of Activities Daily Living (ADL) Patients Post Operation Femur Fracture - Ikrima Rahmasari; Y Gopalan; Agustin T; Francisca W; Maharani MK (Proceeding of International Conference on Science, Health, And Technology, 2021)
Fractures can cause various disorders of body functions. Most fractures are caused by trauma where there is excessive pressure on the bone. One of the most common fractures is a fracture of the femur. In postoperative patients, fractures (fracture of the femur) have increased in activity so that it needs to be gradually restored through joint mobilization, namely Range of Motion (ROM) exercises to restore the patient's Activity Daily Living (ADL) ability. Objective to investigate and see the effect of ROM at early age on the ADL ability of patients after femoral fracture surgery. This study is a quasi-experimental study with a post-test control only design method. A sample of 24 respondents divided into two groups, namely the treatment group and the control group, each of 12 respondents. Respondents who were the subject of the study were postoperative patients with independent and dependent categories of femoral stem fracture. The data collection tool is the ADL observation sheet in the form of the Katz Index after the 4th day. The collected data were analyzed by independent T-test. The results of the analysis obtained that the value of Ho (null hypothesis) is rejected and Ha is accepted, which means that there is an effect of patient ADL between the control group and the treatment group. This means that ROM is needed to restore the ADL ability of patients after femoral fracture surgery.